Effect of diltiazem and metoprolol on left atrial appendix functions in patients with nonvalvular chronic atrial fibrillation - Karaca, Iigin; Coskun, Naci; Yavuzkir, Mustafa; IIkay, Erdogan; Dagli, Necati; Isik, Ahmet; Arslan, Nadi (Turkish Soc Cardiology, 2007)
Objectives: Thrombo-embolic events are the important cause of mortality and morbidity in patients with chronic atrial fibrillation (CAF). The origin of thromboembolism is often the left atrial appendix (LAA), Flow rate velocity (FRV) inside the LAA is the major determinant of thrombus formation. The aim of our study was to investigate the effects of diltiazem and metoprolol used for ventricular rate control on FRV of the LAA in CAF patients and thus to evaluate the positive or negative effects of these two drugs on thromboembolic events. Methods: Sixty-four patients were included in the study. All patients were suffering from CAF for more than a year. The patients were allocated to two groups according with agent used for rate control - metoprolol (Group 1; n=31) and diltiazem (Group 2; n=33). Transesophageal echocardiography was applied to all patients and LAA FRV was measured by a pulse wave Doppler in the 1/3 proximal portion of the LAA. The measurements were repeated after applying 5 mg metoprolol to Group I and 25 mg diltiazem to Group 2 via venous cannula. Results: In Group 1 after metoprolol LAA flow velocity changed from 0.25 +/- 0.90 m/s to 0.25 +/- 0.10 m/s (p>0.05). In group 2 after diltiazem left atrial appendix FRV decreased from 0.21 +/- 0.9 m/s to 0.19 +/- 0.6 m/s (p>0.05). Conclusions: In patients with CAF metoprolol used for ventricular rate control had no effect on LAA flow velocity and the observed decrease in LAA flow rate velocity with intravenous diltiazem was insignificant.
Keywords: atrial fibrillation; left atrial appendage; diltiazem; metoprolol